Molecular Characterization and Transcriptional Regulation Analysis of the Bovine PDHB Gene - Li, Anning (PLoS One, 2016)
The pyruvate dehydrogenase beta subunit (PDHB) is a subunit of pyruvate dehydrogenase (E1), which catalyzes pyruvate into acetyl-CoA and provides a linkage between the tricarboxylic acid cycle (TCA) and the glycolysis pathway. Previous studies demonstrated PDHB to be positively related to the intramuscular fat (IMF) content. However, the transcriptional regulation of PDHB remains unclear. In our present study, the cDNA of bovine PDHB was cloned and the genomic structure was analyzed. The phylogenetic tree showed bovine PDHB to be closely related to goat and sheep, and least related to chicken. Spatial expression pattern analysis revealed the products of bovine PDHB to be widely expressed with the highest level in the fat of testis. To understand the transcriptional regulation of bovine PDHB, 1899 base pairs (bp) of the 5’-regulatory region was cloned. Sequence analysis neither found consensus TATA-box nor CCAAT-box in the 5’-flanking region of bovine PDHB. However, a CpG island was predicted from nucleotides -284 to +117. Serial deletion constructs of the 5’-flanking region, evaluated in dual-luciferase reporter assay, revealed the core promoter to be located 490bp upstream from the transcription initiation site (+1). Electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation assay (ChIP) in combination with asite-directed mutation experiment indicated both myogenin (MYOG) and the CCAAT/enhancer-binding protein beta (C/EBPß) to be important transcription factors for bovine PDHB in skeletal muscle cells and adipocytes. Our results provide an important basis for further investigation of the bovine PDHB function and regulation in cattle.